(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
This article explores the linguistic expressions of happiness in the English and Uzbek languages, shedding light on the cultural nuances and semantic variations that shape the concept of happiness in these two distinct linguistic and cultural contexts. Through a comparative analysis of idiomatic expressions, lexical choices, and cultural connotations, this study aims to provide insights into how happiness is linguistically constructed and understood in English and Uzbek societies. Through a comparative analysis of lexical choices, idiomatic expressions, and cultural perspectives, the study examines how happiness is constructed and understood in these two distinct linguistic contexts. By delving into the social implications and cross-cultural communication challenges inherent in discussing happiness, the research aims to enhance intercultural understanding and shed light on the complex interplay between language, culture, and emotional well-being. Ultimately, this investigation contributes to a deeper appreciation of the diversity of cultural values and linguistic constructions surrounding the concept of happiness.